A facile methodology for the design of functionalized hollow silica spheres - Melvin A.; Vijay R.; Chaudhari V.R.; Gupta B.; Prakash R.; Haram S.; Baskar G.; Khushalani D. (My University, 2025)
A new amino acid derived amphiphile, lauryl ester of tyrosine (LET) is shown to provide a facile methodology for the preparation of hollow silica spheres. In a previous study on the interface adsorption, it was shown that phenolic OH group in LET plays a key role in the formation and stabilization of close packed structures, typically at the oil/water interface. Drawing an analogy between the air/water and the oil/water interface, we detail here a procedure where air droplets are capped with LET aggregated structures, and in turn they are utilized as viable templates in the production of hollow silica spheres. We demonstrate that hollow silica spheres are formed at pH 4.0 specifically under conditions of vortexing within a short period of time (ca. 15. min). The dimensions of the structures are 0.43 ± 0.15μm in diameter and they have then subsequently been used as templates for directing the synthesis of silica-silver and silica-polyanthranilic composite hollow spheres. © 2010 Elsevier Inc.